2021
DOI: 10.5334/jbsr.2405
|View full text |Cite
|
Sign up to set email alerts
|

Getting Rid of Patient’s Misconceptions About the Radiology Department Using Animated Video in the Waiting Room

Abstract: OBJECTIVES:Patients often confuse the role of the radiologist with that of the technician. The aim of this study is to explore patients' current perceptions about the radiology department and to evaluate how it's possible to get rid of misconceptions using informative animated video in the waiting room. MATERIALS AND METHODS:In this multi-centric study (UZ Leuven, ZNA Middelheim), 278 patients of all ages and education levels were surveyed in the radiology waiting room. 107 patients filled out the survey after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Notably, Delcambre et al (2020) found that patients were more likely to view videos shorter than 4 min. For this reason, we limited our video to 1 m and 56 s. Short, animated, fun-to-watch videos are easy, cost-effective tools for providing important information to multiple patients (Lavaerts et al, 2021). Notably, patients have better short-term retention of information after watching animated videos compared with nonanimated videos (Lavaerts et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, Delcambre et al (2020) found that patients were more likely to view videos shorter than 4 min. For this reason, we limited our video to 1 m and 56 s. Short, animated, fun-to-watch videos are easy, cost-effective tools for providing important information to multiple patients (Lavaerts et al, 2021). Notably, patients have better short-term retention of information after watching animated videos compared with nonanimated videos (Lavaerts et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we limited our video to 1 m and 56 s. Short, animated, fun-to-watch videos are easy, cost-effective tools for providing important information to multiple patients (Lavaerts et al, 2021). Notably, patients have better short-term retention of information after watching animated videos compared with nonanimated videos (Lavaerts et al, 2021). Our video included an animated scenario of a patient encounter from check-in to check-out with short informative voice-overs and on-screen text.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation